2010
DOI: 10.1111/j.1538-7836.2010.03791.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet pharmacogenomics

Abstract: Summary. Platelet responsiveness to conventional antiplatelet therapy underlies a high interindividual variability influenced by various factors. For instance, antiplatelet therapy does not curtail the expected effects in a relevant number of patients as demonstrated by the occurrence of repeated cardiovascular events including stent thrombosis and/or by inadequate platelet inhibition measured by in vitro platelet function assays. Besides non-genetic factors such as age, gender, liver and renal function and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 105 publications
0
13
0
3
Order By: Relevance
“…Besides CYP2C19 [157][158][159], polymorphisms of ABCB1 have been sought to explain the inter-individual variability [160,161]. Two studies reported lower plasma clopidogrel concentrations in subjects with the 3435TT genotype [160,162].…”
Section: Clopidogrelmentioning
confidence: 99%
“…Besides CYP2C19 [157][158][159], polymorphisms of ABCB1 have been sought to explain the inter-individual variability [160,161]. Two studies reported lower plasma clopidogrel concentrations in subjects with the 3435TT genotype [160,162].…”
Section: Clopidogrelmentioning
confidence: 99%
“…Yet, this combination fails to prevent ischemic events in most treated patients, and both drugs cause bleeding. Given that clopidogrel is a prodrug oxidized to the active metabolite by cytochrome P450s and that the most significant of these enzymes (CYP2C19) [5] has multiple loss-of-function alleles (http://www.cypalleles.ki.se/cyp2c19.htm), it was proposed that the CYP2C19 genotype would predict efficacy and enable individualized dosing to maximize efficacy while minimizing adverse effects. However, clinical testing of these ideas yielded nonreplicable results [6,7].…”
Section: Clinical Research Is Limited By Deficient Data Collectionmentioning
confidence: 99%
“…Вторая группа -гены семейства цитохрома Р-450 (CYP2C19, CYP2C9, CYP3A4, CYP3A5), через которые идет метаболизм кло-пидогрела. Третья группа -гены, определяющие фар-макодинамику клопидогрела -гены, кодирующие рецепторы тромбоцитов P2Y12, GPIIIa [11].…”
Section: метаболизм клопидогрелаunclassified